Analysis of rotorcraft pilot couplings from the flight control system modes perspective - Yu, Y.; Pavel, M.D.; Kampen, E.J. van; Masarati, P. (My University, 2019)
This paper investigates Rotorcraft Pilot Coupling (RPC) with different Flight Control System (FCS) modes. A generic 16DOF nonlinear helicopter model configured with Rate Command Attitude Hold (RCAH), Attitude Command Attitude Hold (ACAH) and Translational Rate Command (TRC) mode has been developed to run simulations on triggering PIO. In addition, ROVER has been extended to multi-axis ROVER to detect PIO. The control mode sensitivity and tolerability to pilot time delay, actuator saturation, actuator rate limit, control authority of the Stability and Control Augmentation System (SCAS) and sensor dynamics are studied. Results show that: 1) the tolerance to the pilot time delay is highest for the TRC mode, followed by ACAH and RCAH; 2) inner vehicle trigger factors (actuator saturation, actuator rate limit, control authority and sensor dynamics) play a more important role than external trigger factors (pilot time delay) in triggering PIO; 3) inner vehicle trigger factors make the RCAH, ACAH and TRC mode more sensitive to pilot time delay; 4) the tolerability of different control modes to abnormal actuator saturation is the same; 5) for actuator rate limit and control authority, the TRC mode has the highest tolerance, followed by ACAH and RCAH; 6) TRC mode and RCAH mode have the same tolerability to abnormal sensor dynamics while the tolerability of ACAH is lower. These findings offer guidance for designing pilot-in-the-loop simulator experiments that will further investigate RPCs related to different control modes.